Implementasi Model Pembelajaran Kooperatif Tipe Jigsaw Berbantuan Media Whatsapp Dan Zoom Meeting Pada Pembelajaran Bahasa Inggris Kelas XI Agama Di MAN DOMPU - Rusdin, Rusdin; Sahrul Hafiz, Hairori (BULLET : Jurnal Multidisiplin Ilmu, 2023)
This research is to find out the increase in student learning outcomes after applying the jigsaw in learning English for class XI Religion MAN Dompu online by using WhatsApp media and zoom meetings. The type of this research is descriptive qualitative research. The subjects of this study were students of class XI Religion at MAN Dompu for the 2022/2023 academic year. This type of jigsaw learning is an active type of learning that forms heterogeneous study groups consisting of 4-5 people. Each student is responsible for mastering part of the learning material so that they can collaborate with other members. The results of this study using the method are as follows: Increasing the self-ability of each individual, accepting each other's shortcomings towards more significant individual differences, reducing interpersonal conflict, reduced apathy, deeper understanding, greater motivation, higher learning outcomes, retention or longer storage, increasing kindness, sensitivity and tolerance, and cooperative learning.